Gut microbiota profiling variated during colorectal cancer development in mouse - Jingjing Liu; Wei Dong; Jian Zhao; Jing Wu; Jinqiang Xia; Shaofei Xie; Xiaofeng Song (BMC Genomics, 2022)
Abstract Background The imbalance of intestinal flora may promote the occurrence and development of colorectal cancer, changes of the intestinal flora during the development of colorectal cancer and the mechanism that promotes the colorectal cancer were discovered in this study. Deep sequencing of the microbial 16 s ribosomal RNA gene was used to investigate alterations in feces samples of mice at the early inflammation stage and fully developed stage of colorectal cancer. Results According to PCoA analysis and ANOSIM test, we found the intestinal flora had significantly changed in mice with colorectal inflammation or colorectal cancer compared with healthy mice (p < 0.05). Using correlation analysis, we found that Muribaculaceae and Bacteroidaceae had strong excluding interactions. The functional changes of the gut microbiota include the up-regulation of the cancers pathway and the down-regulation of the replication and repair pathways. Conclusion Our study found the intestinal flora of mice suffering from colorectal inflammation and colorectal cancer has changed significantly, especially the decrease of Muribaculaceae and the increase of Bacteroidaceae. We suppose that these two floras may play an important role in development of colorectal cancer.